The effect of bcl-2 over-expression on hybridoma cell line cultured in different serum free media - Abdul Majid, Fadzilah Adibah; Al-Rubeai, Mohamed (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
One of the criteria for large scale production of therapeutics using animal cell lines is the ability to grow in and can be maintained in inexpensive, serum free defined medium. Serum free medium however, compromised by the high levels of cell death seen in bioreactors, which is mainly via apoptosis. Previous studies in our laboratory have demonstrated that apoptosis in bioreactors can be prevented by bcl-2 over-expression in these cell lines. The robustness of the bcl-2 transfected hybridoma (TB/C3) cell line could allow them to be grown in simple medium formulation especially without serum supplementation which could facilitate the down stream processing, overall manufacturing process and product consistency. In the present study, the impact of the suppression of apoptosis on cell adaptation to various media formulation was carried out. This cell line was successfully grown in suspension batch culture with WMC5, HybSFM, DMEM/F12, WMC5/RPMI 1640 media and in serial dilution of HybSFM without prior adaptation.